Faktor-Faktor yang Mempengaruhi Emisi Karbon di ASEAN dengan Penanaman Modal Asing sebagai Variabel Moderasi - Finna Afifah S; Maizul Rahmizal (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the factors that influence carbon emissions in the ASEAN region with Foreign Direct Investment (FDI) as a moderating variable. The independent variables used include energy consumption, Gross Domestic Product (GDP) per capita, Information and Communication Technology (ICT), and political corruption levels. Panel data were collected from 10 ASEAN countries over the period 2013–2022 and analyzed using multiple linear regression and moderation regression. The results indicate that energy consumption, ICT and FDI have a positive and significant effect on carbon emissions, while GDP per capita and corruption have a negative and significant effect. Interaction tests revealed that the ICT x FDI variable has a positive and significant effect on carbon emissions, but the interactions between GDP x FDI, energy consumption x FDI, and corruption x FDI are not significantly influential.